OPTIMALISASI WINDOWS LIGHTING DALAM FOTOGRAFI POTRET UNTUK MENGHADIRKAN BENTUK KARAKTER WAJAH - Nofria Doni Fitri; Katrin Nur Nafi’ah Ismoyo (LP2M Sekolah Tinggi Seni Rupa dan Desain Visi Indonesia (STSRD VISI), 2026)
Almost everyone has a self-portrait. This design aims to provide an ideal formulation for facial lighting using window lighting techniques. The method used is to place the model at the edge of a window and direct the center of the model's face towards the light source from the window. Determining the distance of the face from the edge of the window and adjusting the width of the window shutter to twice the width of the head to control the right light to illuminate the face. This can create a long and soft tonal gradation of black-and-white photos and can inform the facial shape well. The implementation of this design was applied to three elderly models and then analyzed the results. This design obtained the ideal lighting technique for portrait photos with good detail and optimal light and dark, so that the face appears to emerge from the darkness. The dominant dark nuances around the face make the attention focused only on the model's face.